WNT5A Has Anti‐Prostate Cancer Effects In Vitro and Reduces Tumor Growth in the Skeleton In Vivo. (16th February 2015) - Thiele, Stefanie; Göbel, Andy; Rachner, Tilman D; Fuessel, Susanne; Froehner, Michael; Muders, Michael H; Baretton, Gustavo B; Bernhardt, Ricardo; Jakob, Franz; Glüer, Claus C; Bornhäuser, Martin; Rauner, Martina; et al.
ABSTRACT: Prostate cancer is the most frequent malignancy in men, and a major cause of prostate cancer–related death is attributable to bone metastases. WNT5A is known to influence the clinical outcome of various cancer types, including prostate cancer, but the exact mechanisms remain unknown. The goal of this study was to assess the relevance of WNT5A for the development and progression of prostate cancer. WNT5A expression was determined in a cDNA and tissue microarray of primary tumor samples in well‐defined cohorts of patients with prostate cancer. Compared with benign prostate tissue, the expression of WNT5A and its receptor Frizzled‐5 was higher in prostate cancer, and patients with a WNT5A expression above the median had a higher probability of survival after 10 years. Using different osteotropic human prostate cancer cell lines, the influence of WNT5A overexpression and knock‐down on proliferation, migration, and apoptosis was assessed. In vitro, WNT5A overexpression induced prostate cancer cell apoptosis and reduced proliferation and migration, whereas WNT5A knock‐down showed opposite effects. In vivo, different xenograft models were used to determine the effects of WNT5A on tumor growth. Local tumor growth and tumor growth in the bone microenvironment was considerably diminished after WNT5A overexpression in PC3 cells. WNT5A exhibits antitumor effects in prostate cancer cells and may be suitable as a prognostic marker and therapeutic target for prostate cancer and associated skeletal metastases. © 2014 American Society for Bone and Mineral Research.